Analysis of The Effectiveness of Motor Vehicle Tax Revenue and Motor Vehicle Title Transfer Fee at SAMSAT Rangkasbitung - Arofahmawati, Fina Amal; Prihatni, Rida; Zahra, Siti Fatimah (LPPM Universitas Negeri Jakarta, 2023)
ABSTRACT The purpose of this study was to analyze the effectiveness of Motor Vehicle Tax (PKB) and Motor Vehicle Title Transfer Fee (BBNKB) revenue and to develop efforts to increase PKB and BBNKB revenues at Samsat Rangkasbitung for the period 2018-2022. One measure of the success of PKB and BBNKB revenue is by calculating the effectiveness of PKB and BBNKB. The research method used is quantitative research with a descriptive approach. Meanwhile, the samples used were the target and realization reports of motor vehicle taxes and motor vehicle title transfer fees in 2018-2022 at Samsat Rangkasbitung. Sampling was done by purposive sampling. The results showed that the effectiveness of PKB and BBNKB revenue at Samsat Rangkasbitung was in the criteria of very effective and quite effective so that it could increase local revenue. In addition, in increasing the revenue of PKB and BBNKB, Samsat Rangkasbitung made various efforts including conducting socialization to the community, launching Samsat Drive Thru, and others.